2018
DOI: 10.14716/ijtech.v9i2.990
|View full text |Cite
|
Sign up to set email alerts
|

A New Cascade Solar Desalination System with Integrated Thermosyphons

Abstract: Current cascade solar desalination systems can convert sea water into fresh water, but they can only produce small quantities. To produce more fresh water, there is a solution that can be applied, i.e. modification of the existing desalination system by adding thermosyphons. The objective of this research is to design a cascade solar desalination system with integrated thermosyphons and to establish its ability to produce fresh water. The experimental study was conducted by adding an aluminum absorber plate as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Figures [4][5][6] also show that, for variations of heat load, higher heat load affects the increasing of evaporator, condenser, and adiabatic temperatures until isothermal condition is reached. It can be seen that the increasing of heat load after stable temperature distribution achieved would not affect the recurrent of overshoot phenomena, but only on recurrence of zigzag and stable phenomena and the increasing of the overall heat pipe temperature.…”
Section: Preparation Of Graphene Nanofluidmentioning
confidence: 94%
“…Figures [4][5][6] also show that, for variations of heat load, higher heat load affects the increasing of evaporator, condenser, and adiabatic temperatures until isothermal condition is reached. It can be seen that the increasing of heat load after stable temperature distribution achieved would not affect the recurrent of overshoot phenomena, but only on recurrence of zigzag and stable phenomena and the increasing of the overall heat pipe temperature.…”
Section: Preparation Of Graphene Nanofluidmentioning
confidence: 94%
“…There are also solar-powered humidification-dehumidification (HDH) desalination systems (El-Fiqi et al, 2007) and industrial waste heat (Gude, 2011), and solar-driven membrane distillation (He et al, 2015). (Kusuma, Putra and Respati, 2018) study modified the existing desalination system by adding thermosyphons. The results show that the use of thermosyphons in cascade solar desalination systems can increase the efficiency of the thermal system up to 2.35 times.…”
Section: Introductionmentioning
confidence: 99%
“…Those studies revealed that the heat pipe could be adapted its shape to the heat source geometry that existed. Whatever its heat pipe type, it can absorb and release heat well to the environment, or the heat that is sunk can be used as another energy generator (for example, it is used as a heat source in thermal desalination) [4,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%